Does Metabolic Syndrome Increase the Risk of Postoperative Complications in Patients Undergoing Colorectal Cancer Surgery?. Issue 7 (July 2019) - Shariq, Omair A.; Hanson, Kristine T.; McKenna, Nicholas P.; Kelley, Scott R.; Dozois, Eric J.; Lightner, Amy L.; Mathis, Kellie L.; Habermann, Elizabeth B.
Abstract : BACKGROUND: Metabolic syndrome is associated with poorer postoperative outcomes after various abdominal operations. However, the impact of metabolic syndrome on outcomes after colorectal cancer surgery remains poorly described. OBJECTIVE: The purpose of this study was to determine the association between metabolic syndrome and short-term postoperative outcomes in patients undergoing elective colorectal cancer surgery. DESIGN: This was a retrospective cohort study. SETTINGS: This study used a national multicenter database. PATIENTS: Adult patients who underwent elective colectomy for colorectal cancer from 2010 to 2016 were identified in the American College of Surgeons National Surgical Quality Improvement Program database. MAIN OUTCOME MEASURES: Thirty-day postoperative mortality and morbidity, unplanned reoperation, unplanned readmission, operative time, and length of stay were measured. RESULTS: A total of 91, 566 patients were analyzed; 7603 (8.3%) had metabolic syndrome. On unadjusted analysis, metabolic syndrome was associated with an increased risk of 30-day overall morbidity, pulmonary complications, renal complications, septic complications, cardiac complications, wound complications, blood transfusion, longer length of stay, and unplanned readmissions. On multivariable analysis, metabolic syndrome remained significantly associated with renal complications (OR = 1.44 (95% CI, 1.29–1.60)), superficial surgical site infection (OR = 1.46 (95% CI, 1.32–1.60)), deep surgical site infection (OR = 1.40 (95% CI, 1.15–1.70)), wound dehiscence (OR = 1.47 (95% CI, 1.20–1.80)), and unplanned readmissions (HR = 1.24 (95% CI, 1.15–1.34)). The risks of overall morbidity, cardiac and septic complications, and prolonged length of stay for laparoscopic procedures were significantly associated with diabetes mellitus rather than metabolic syndrome as a composite entity. LIMITATIONS: This study was limited by its retrospective design and inability to analyze outcomes beyond 30 days. CONCLUSIONS: Patients with metabolic syndrome undergoing elective surgery for colorectal cancer have an increased risk of 30-day postoperative renal complications, wound complications, and unplanned hospital readmissions. A multidisciplinary approach involving lifestyle modifications and pharmacologic interventions to improve the components of metabolic syndrome should be implemented preoperatively for these patients. See Video Abstract at http://links.lww.com/DCR/A909 . Abstract : Supplemental Digital Content is available in the text.